SCAI expert consensus statement for advanced training programs in pediatric and congenital interventional cardiac catheterization. Issue 5 (26th June 2014) - Armsby, Laurie; Beekman, Robert H.; Benson, Lee; Fagan, Thomas; Hagler, Donald J.; Hijazi, Ziyad M.; Holzer, Ralf; Ing, Frank; Kreutzer, Jacqueline; Lang, Peter; Levi, Daniel S.; Latson, Larry; et al.
<x xml:space="preserve">Abstract</x> Pediatric and Congenital Interventional Cardiology is the practice of catheter‐based techniques that improve cardiac physiology and circulation through the treatment of heart disease in children and adults with congenital or acquired heart defects. Over the last decade, and since last published training guidelines for pediatric cardiac catheterization and interventional cardiology were published in 2005 [1] the field of Pediatric and Congenital Cardiac Catheterization has evolved into a predominantly interventional discipline. As there is no sub‐specialty certification for interventional cardiac catheterization in pediatrics, the Congenital Heart Disease Committee of the Society of Cardiovascular Angiography and Interventions has put together this consensus statement for advanced training in pediatric and congenital interventional cardiac catheterization. The statement puts forth recommendations for program infrastructure in terms of teaching, personnel, equipment, facilities, conferences, patient volume and trainee assessment. This is meant to set a standard for training programs as well as giving applicants a basis on which to judge and compare programs. © 2014 Wiley Periodicals, Inc.